A violência da segregação. Uma etnografia da comunidade do Timbó localizada no bairro de Bancários em João Pessoa/PB. - Soares, Cristiane Leal Rodrigues (2009)
This research approaches the questions sociological: segregation and urban violence, having as lócus Bank clerks, one of the quarters of João Person, capital of the Paraíba. The general objective of the research was to analyze which the relation between segregation and violence in this quarter. The motivation how much to the choice of this object of comment, it left of some tracks that pointed with respect to the existence of segregation in Bank clerks, raised in previous research, and of the knowledge gotten for proper experience of the reality of the quarter how much to the constant occurred cases of violence in its space. For the accomplishment of this research the etnográfico method was used. Soon after the confirmation of the segregation existence space partner in Bank clerks, I attempted against in considering this phenomenon as a violence form, in the measure in express the sufferings of the daily reality of one of the communities of the quarter, the Timbó. The research looked for to also understand the factors and the agents who determine the segregation of this community. Moreover, it verified that this segregation contributes for the sprouting of other forms of urban violence, that if constitute in crimes, many of violent them. Such crimes for its time strengthen the segregation and the stigma on the segregated community of the quarter.